Systematic Review and Expert Consensus on the Use of Long-acting Monoclonal Antibodies for Prevention of Respiratory Syncytial Virus Disease: ARMADA (Advancing RSV Management And Disease Awareness) Taskforce - Manzoni, Paolo; Baraldi, Eugenio; Midulla, Fabio; Claris, Olivier; Dessardo, Sandro; Heikkinen, Terho; Thwaites, Richard; Paes, Bosco; Carbonell-Estrany, Xavier; Dobryanskyy, Dmytro; Cetinkaya, Merih; Al Harbi, Adel S.; et al. (Oxford University Press (OUP), 2026)
Background: Long-acting monoclonal antibodies (LAmAbs) could dramatically reduce the respiratory syncytial virus (RSV) disease burden in children if implemented using clear, evidence-based recommendations.
Methods: The ARMADA Taskforce-an international, multidisciplinary expert panel-undertook a systematic review to develop LAmAbs consensus recommendations for RSV disease prevention in children.
Results: The Taskforce recommends LAmAbs for all infants aged <8 months in the absence of maternal RSV vaccination, preterm infants (<37 weeks' gestational age) aged <12 months, and children <24 months with high-risk conditions. Seasonal LAmAb administration is recommended, although in RSV-endemic countries decisions should be made locally concerning administration year-round or with peak RSV incidences.
Conclusions: The Taskforce strongly endorses LAmAbs implementation based on their efficacy, effectiveness, and public health impact. These recommendations provide a blueprint to inform guidelines worldwide. Wider equitable access to LAmAbs at affordable prices, especially in low- and middle-income countries is needed to reduce the childhood RSV burden.